2016
DOI: 10.1007/s12307-016-0187-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Acidic pH on Proliferation, Invasion and Drug-Induced Apoptosis in Lymphoblastic Leukemia

Abstract: Some studies have shown that extracellular pH in tumors, which results in tumor progression, is less than that in normal tissues. The aim of this study was to investigate the effects of extracellular acidic pH on proliferation, invasion, and drug-induced apoptosis in acute lymphoblastic cells. The cells were cultured in different pH (pH 6.6 and pH 7.4) for 12 days. Cell proliferation was assessed by MTT assay and cell invasion was assayed by invasion assay and gene expression analysis of MMP-9. Drug-induced ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…It has been shown that extracellular pH of cancer cells is slightly acidic (pH 6.2–6.9) than that of normal cells (pH 7.2–7.5). Acidic environment not only promotes cancer cell transcription of tumor-promoting factors such as VEGF, IL-8 and hypoxia-inducible factor (HIF-1) [ 262 264 ], but increases the expression of proteases like MMPs and cathepsins that facilitate migration of the cancer cells [ 265 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that extracellular pH of cancer cells is slightly acidic (pH 6.2–6.9) than that of normal cells (pH 7.2–7.5). Acidic environment not only promotes cancer cell transcription of tumor-promoting factors such as VEGF, IL-8 and hypoxia-inducible factor (HIF-1) [ 262 264 ], but increases the expression of proteases like MMPs and cathepsins that facilitate migration of the cancer cells [ 265 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Other studies have shown that the extracellular acid environment can reduce the apoptotic potential, change the genetic properties, and increase the activity of multidrug transporters to make tumor cells resistant to drug resistance, thereby evading the damage of chemotherapy drugs. 9,10 In addition, studies have shown that the extracellular acid environment can increase the expression of interleukin 8 (IL-8), vascular endothelial growth factor (VEGF), cathepsin B (CTSB), matrix metalloproteinase 2 (MMP2) and matrix metalloproteinase 9 (MMP9). 11,12 In short, the extracellular low-acid environment contributes to chemotherapy resistance, but the molecular mechanism is still unclear.…”
Section: Intruductoinmentioning
confidence: 99%
“…While several studies have demonstrated that a low extracellular pH favors the induction of apoptosis (Ding et al, 2000;Thatte et al, 2004;Kumar et al, 2007), in other studies acidification has been found to inhibit apoptosis. A protective effect of acidosis has been observed in different cell types including endothelial cells (D'Arcangelo et al, 2000;D'Arcangelo et al, 2002;Terminella et al, 2002;Kumar et al, 2008), liver cells (Currin et al, 1991), lymphoblastic cells (Bohloli et al, 2016), neurons (Xu et al, 1998), colon adenocarcinoma cells (Sharma et al, 2005) and osteoclasts (Pereverzev et al, 2008). The mechanisms underlying the protective effect of acidosis against apoptosis are still unclear.…”
Section: Introductionmentioning
confidence: 99%